Mechanical Properties and Dielectric Properties of Bismaleimide Composites Modified by Multi-walled Carbon Nanotubes and Polyethersulfone - CHEN Yu-fei; GUO Hong-yuan; HAN Yang; TENG Cheng-jun (Journal of Harbin University of Science and Technology)
3,3’.diallyl bisphenol A (BBA) and bisphenol.A diallyl ether (BBE) were used as reactive diluent to toughen 4,4’.diamino diphenyl methane bismaleimide (MBMI) and obtained MBMI.BBA.BBE(MBAE) polymer matrix. Polyether sulfone (PES) and acid.MWCNTs as modifier, MWCNTs/PES.MBAE composite was prepared through in.situ polymerization method. The mechanical properties of MWCNTs/PES.MBAE composites were characterized by impact strength and flexural strength. The results showed that the impact strength and bending strength were both changed with the content of MWCNTs and showed a trend of first increases and then decreases, increased by 74% and 53%, respectively, when the content of acid.MWCNTs was 0.02wt%. The change of dielectric constant for composite was not remarkable in low frequency area, when the frequency was more than 10.4.Hz they decreased obviously. Dielectric loss of composites increased slightly, but they were less than 1×10.-3 this composites could be used as a conventional insulation materials.